2016
DOI: 10.1111/ejn.13369
|View full text |Cite
|
Sign up to set email alerts
|

Threshold tracking primary motor cortex inhibition: the influence of current direction

Abstract: Paired-pulse transcranial magnetic stimulation (TMS) can be used to probe inhibitory activity in primary motor cortex (M1). Recruitment of descending volleys with TMS depends on the induced current direction in M1. Anterior-posterior (AP) stimulation preferentially activates late indirect- (I-) waves that are most susceptible to paired-pulse TMS. Threshold tracking TMS can assess intracortical inhibition; however, previous studies have only used a current direction that preferentially recruits early I-waves [p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
59
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 43 publications
6
59
1
Order By: Relevance
“…; Hamada et al . ; Cirillo & Byblow, ) and probably represent D‐wave recruitment following LM, early I‐wave recruitment following PA and late I‐wave recruitment following AP in both subject groups. Taken together, these findings suggest that the preferential recruitment of interneuronal circuits activated when varying the direction of the cortical current induced by TMS (i.e.…”
Section: Discussionmentioning
confidence: 84%
“…; Hamada et al . ; Cirillo & Byblow, ) and probably represent D‐wave recruitment following LM, early I‐wave recruitment following PA and late I‐wave recruitment following AP in both subject groups. Taken together, these findings suggest that the preferential recruitment of interneuronal circuits activated when varying the direction of the cortical current induced by TMS (i.e.…”
Section: Discussionmentioning
confidence: 84%
“…In this study, the exclusion rate due to coil overheating was relatively high and biased towards subjects with high RMT 0.2mV , posing a potential limitation to the results. CS intensities for A-SICI were set based on RMT 0.2mV which, according to limited reports, is equal to about 109% RMT 0.05mV [ 50 , 51 ]. This should be kept in mind when comparing our results to the studies where RMT 0.05mV was used.…”
Section: Discussionmentioning
confidence: 99%
“…A further complicating factor which will need investigation is coil orientation. In common with the majority of TMS studies, our SICI measurements were obtained exclusively using the posterior-anterior current direction, whereas it has been reported that the anterior-posterior direction may result in more robust inhibition [23,24].…”
Section: Detection Of Abnormal Lack Of Sicimentioning
confidence: 99%